Induction Resistance in Chili (Capsicum frutescens L.) to the Geminivirus Disease by Pseudomonas fluorescens - Saidi, Aluna Uthilma; Martosudiro, Mintarto; Abadi, Abdul Latief (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
This study included resistance induced by Pseudomonas fluorescens PGPR in chili (Capsicum frutescens L.) infected with Geminivirus. Geminivirus often attacks chili plants, causing disease with a yellowish color to the leaves, lobes, and stunting. Chili plants that have been attacked by the virus will experience crop failure and plant death. Virus prevention can be done with the application of PGPR by Pseudomonas fluorescens. The method used was 6 treatments on chili plants which were repeated 4 times. The analysis of variance was processed using R software. The results showed that cayenne pepper plants that were given the PGPR application had a shorter incubation period against Geminivirus attacks. Each concentration of Pseudomonas fluorescens has a mean incubation period that is not significantly different. The results also showed that there was a significant difference in the intensity of the disease that attacked the cayenne pepper plant. The application of 107 Pseudomonas fluorescens showed the most optimal results for phenol content, plant height, and number of plant leaves. The application of 109 Pseudomonas fluorescens showed optimal results for the content of IAA and the content of the peroxidase enzyme.